Pendidik Dalam Upaya Pembentukan Karakter Rabani Generasi Muda Melalui Penerapan Metode Lagu Islami - Makhmudah, Siti (J-PAI: Jurnal Pendidikan Agama Islam, 2021)
The era of the Industrial Revolution 4.0 has had a tremendous impact on human life. The impact has caused major changes in all aspects of community life, both positive and negative impacts. Information becomes widely spread quickly and can be accessed easily by the public. However, behind such a positive impact, the negative impact cannot be avoided, including: the development of unnecessary information, such as content containing acts of violence, pornography, pornoaction and hoax news. This negative impact can trigger a moral recitation among Indonesia's younger generations. Therefore, character education efforts are needed from an early age as a bulwark against latent demoralization attacks. One of the effective ways of cultivating character is through early childhood education. Education institutions apply basic learning from character building so that children have basic abilities according to their development stage. This study uses a Classroom Action Research type of research and aims to implement the method of learning Islamic songs as an effort to build character in early childhood. The results of this study indicate that: 1) the learning atmosphere becomes more lively so that children can follow the lessons well; 2) Stimulating children's social spirit so as to create an equal atmosphere among friends; 3) Through learning Islamic songs in the form of clapping, songs and gestures, moral messages for character building are easy to memorize and apply.